(untitled) (Scientific journal of the Fergana State University, 2023)
Inductively coupled plasma mass-spectrometry (ICP MS) was used to quantify 44 macro and microelements in the flowers of Tansy. The largest macronutrients in quantitative terms: Ca-9628, K-9297, P-4927, Al-3012, Si-2301. Mg-851, Na-414 mg/kg, The amount of iron at the level of macronutrients Fe-636, The amounts of important trace elements are as follows: Mn-32, Zn-23, Sr-9 mg/kg. A comparative analysis was carried out with samples from other places of growth. Thus, a comparison with Ukrainian samples showed that there are certain differences, but the general trend remains.